2020
DOI: 10.1021/acs.analchem.9b05729
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pressure Increase on Macromolecules’ Adsorption in Ion Exchange Chromatography

Abstract: In this study a new method for evaluating the pressure effect on separations of oligonucleotides and proteins on an anion exchange column was developed. The pressure rise of up to 500 bar was attained by coupling restriction capillaries to the column outlet to minimize differences in pressure over the column. Using pH transient measurements it was demonstrated that no shift in ion exchange equilibria occurs due to a pressure increase. Results from isocratic and gradient separations of oligonucleotides (model c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…The Langmuir adsorption isotherm equation was an ideal model of the surface adsorption for column chromatography packing with HP20 resin. However, in the actual separation and purification process, only a narrow range of adsorption could be recognized on a uniform surface, which indicated that only a narrow range of this equation was applicable [ 26 , 27 ]. Most of it was not applicable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Langmuir adsorption isotherm equation was an ideal model of the surface adsorption for column chromatography packing with HP20 resin. However, in the actual separation and purification process, only a narrow range of adsorption could be recognized on a uniform surface, which indicated that only a narrow range of this equation was applicable [ 26 , 27 ]. Most of it was not applicable.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption and separation function of column chromatography mainly relied on intermolecular force, hydrogen bond, coordination bond, hydrophobic interaction, ionic bond, and other interactions to achieve its adsorption and separation function. Kristl et al tested the range of adsorption heat caused by different types of forces [ 27 ], and found that the adsorption heat caused by van der Waals force was 4–10 KJ/mol, that caused by water-dispersing bond force was about 5 KJ/mol, that caused by hydrogen bond force was 2–40 KJ/mol, that caused by coordination bond exchange was greater than 40 KJ/mol, and that caused by chemical bond force was greater than 60 KJ/mol. The adsorption thermodynamic parameters of the HP20 resin for theasinensin A, theasinensin B, and theasinensin C were 10–40 KJ/mol, which belong to hydrogen bond force adsorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conformational changes upon adsorption were reported in ion exchange (IEX) and in hydrophobic interaction chromatography (HIC) as well. 20 − 22…”
Section: Introductionmentioning
confidence: 99%
“… 21 An increase in retention of biopolymers and macromolecules with pressure was also demonstrated on an anion exchange column where up to an 80% increase in retention time and a 40% increase in resolution were observed. To understand these effects on RP or ion exchange (IEX) columns, the change in retention with pressure was described by equations based on basic thermodynamic principles 11 , 22 24 where Δ G θ , Δ E θ , Δ V θ , and Δ S θ are changes in the standard Gibbs free energy, internal energy, entropy, and volume of the system at a given temperature ( T ) and pressure ( p ). R is the gas constant, and K is the equilibrium constant.…”
Section: Introductionmentioning
confidence: 99%